Color Doppler imaging of the ophthalmic artery in patients with chronic heart failure - Almeida-Freitas,Daniela B. (2011)
Purpose: To evaluate the ophthalmic artery hemodynamics in patients with chronic heart failure. Methods: Doppler parameters of ophthalmic artery of 18 patients with chronic heart failure in different stages of the disease were compared with 21 healthy volunteers (control group). These parameters were also correlated with echocardiographic assessments and clinical cardiologic status. Results: Mean diastolic velocity was 5.14 ± 2.4 cm/s in the chronic heart failure group and 7.44 ± 3.5 cm/s in the control group (p=0.007). Mean resistance index of the ophthalmic artery was 0.76 ± 0.08 in the chronic heart failure group and 0.70 ± 0.08 in the control group (p=0.04). Mean systolic velocity of the ophthalmic artery was 22.03 ± 7.7 cm/s in the chronic heart failure group and 25.32 ± 9.2 cm/s in the control group (p=0.24). There was a negative correlation between the resistance index of the ophthalmic artery and systemic blood pressure of patients with chronic heart failure (r= -0.47, p=0.007). Diastolic velocity of the ophthalmic artery correlated positively with systemic blood pressure (r=0.44, p=0.02). Conclusion: Lower diastolic velocity and higher resistance index were observed in the ophthalmic artery of chronic heart failure patients when compared to the control group, which probably reflects the presence of orbital vasoconstriction in response to low cardiac output. Therefore, the influence of these findings on the structure and function of the optic nerve head deserves investigation.